Otimização de estratégias de oferta em mercado usando previsão probabilística de produção renovável - José Carlos Mendes Bessa (2021)
The daily and intraday market offers of renewable generation aggregates (hydro, photovoltaic and wind) are subject to production uncertainties, with consequences in economic losses due to deviation penalties. The supply strategy, in the sequential cascade of markets, requires knowing as well as possible the expected values of the forecasts and the uncertainties associated with them. To optimize these strategies it is important to have probabilistic models of production aggregates. In this context, it is intended in this dissertation to develop probabilistic models for forecasting hydro, wind and photovoltaic production. A probabilistic forecast aggregation model will also be developed. To evaluate the performance of the models, they will be tested in a test period of a renewable production portfolio of the company PH Energia, Lda, being evaluated the economic benefits of the models in a recent test period.